Genius - Maule, David (New York Cambridge University, 2014)
Shakespeare, Mozart, Madame Curie, Albert Einstein...what do these people have in common? See the world through the eyes of a genius
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level